Age-dependent Effects of Socio-economic Background on Educational Attainment - Evidence from Germany - Wolter H.J. Hassink; H. Kiiver (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2007)
The impact of socio-economic background on a child's educational attainment has been discussed as a static concept so far. Existing economic literature as well as the psychology of education literature point however towards a dynamic process where the impact of socio-economic background depends on the age of the child. We explore this possibility using German micro-data. Using instrumental variable methods we estimate the causal effects of parental education and household income on school success of a child at two points in time of his school career. The estimates indicate that household income has a more important effect on the educational success of children in a more advanced point during the education while the effect of parental education seems to be stable.
Keywords: 330; school choice; demand for schooling; human capital